The Synergy of Islamic Education and Sufism in Fostering Religious Moderation and Preserving Local Culture to Achieve the Sustainable Development Goals: A Study at Pesantren Tebuireng - Jasminto; Siti Rofi'ah; Muath Khalil Amayreh (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to examine the integration of religious moderation and local cultural preservation through the synergy of Islamic education and Sufi (tasawuf) values at Pesantren Tebuireng in supporting the achievement of the Sustainable Development Goals (SDGs). Theoretical framework: The research is grounded in theories of religious moderation, Islamic education, Sufi spirituality, and cultural preservation, emphasizing the interconnectedness of spiritual development, social harmony, and local wisdom. Literature review: Previous studies have discussed religious moderation, pesantren education, and local cultural sustainability independently; however, limited research has comprehensively explored how tasawuf-based Islamic education simultaneously strengthens moderate religious attitudes and preserves local cultural traditions within a formal educational institution. Method: This study employs a qualitative approach using literature analysis, document review, in-depth interviews with pesantren leaders, educators, and students, as well as participant observations of educational activities and cultural practices. The collected data were analyzed through thematic analysis to identify patterns of value integration and educational implementation. Results: The findings reveal that integrating Sufi teachings into Islamic education effectively cultivates religious moderation by promoting tolerance, compassion, humility, and mutual respect while reinforcing the preservation of local cultural traditions through religious rituals, communal practices, and cultural appreciation. These educational practices strengthen students' spiritual character, social responsibility, and cultural resilience, contributing directly to SDG 4 (Quality Education), SDG 11 (Sustainable Cities and Communities), and SDG 16 (Peace, Justice, and Strong Institutions). Implications: The study provides a practical educational model for policymakers and Islamic educational institutions seeking to balance religious values with cultural sustainability and peaceful coexistence. Novelty: This research offers a comprehensive institutional model demonstrating how tasawuf-based Islamic education harmonizes religious moderation with local cultural preservation, presenting a replicable framework for strengthening spiritual character and cultural resilience in diverse educational contexts.